MicroRNA-145-5p and microRNA-320a encapsulated in endothelial microparticles contribute to the progression of vasculitis in acute Kawasaki Disease - Nakaoka, Hideyuki (Sci Rep, 2018)
Kawasaki Disease (KD) is an acute inflammatory disease that takes the form of systemic vasculitis. Endothelial microparticles (EMPs) have been recognized as an important transcellular delivery system. We hypothesized whether EMPs are involved in vasculitis in acute KD. Fifty patients with acute KD were enrolled, divided into two subgroups: those with coronary artery lesions (CAL) (n = 5) and those without CAL (NCAL) (n = 45). EMPs were measured using flow cytometry, and microRNA (miR) expression profiling was performed by microRNA array. The percentage of EMPs in acute KD was significantly higher than in controls (P < 0.0001). EMPs in patients with CAL rapidly increased after the initial treatment, and was significantly higher than those in NCAL (P < 0.001). In patients with CAL, we identified 2 specific miRs encapsulated in EMPs, hsa-miR-145-5p and hsa-miR-320a, which are predicted to affect monocyte function using in silico analysis, and were demonstrated to upregulate inflammatory cytokine mRNAs in THP-1 monocytes. In situ hybridization confirmed that hsa-miR-145-5p was preferentially expressed in CAL. EMPs may serve as a sensitive marker for the severity of vasculitis in acute KD. Moreover, these 2 specific miRs encapsulated in EMPs might be involved in inflammatory cytokine regulation and the pathogenesis of vasculitis in acute KD.